Green synthesis of Ba(Fe1/2Nb1/2)O3 ceramics with high dielectric constant - Jha Anal K.; Prasad Kamal (Processing and Application of Ceramics, 2025)
Domestic and/or kitchen wastes are a burden to the environment and they attract microbes after gradual festering and decomposition adding to the deterioration of the ambient air quality. Waste lemon peels are one of them. In this work, a novel green, reproducible and cost-effective synthetic method for the fabrication of dielectric Ba(Fe1/2Nb1/2)O3 (abbreviated as n-BFN) nanopowder mediated by waste lemon peel is presented. The waste lemon peels are inundated in promising secondary metabolites, each having its own potential in nanopowder preparation. The lemon peels are rich in terpenoids, ascorbic acid, citric acid along with other metabolites which in consonance help to ensure the synthesis of nanoscale compounds. A plausible mechanism for the green synthesis process in n-BFN formation is proposed. X-ray diffraction analyses confirmed the formation of a single-phase BFN with cubic structure (a = 4.0597Å, space group Pm¯3m). Transmission and scanning electron microscopy images revealed both individual nanoparticles and a few aggregates whose sizes varied between 11 and 48 nm. The complex impedance and electric modulus spectroscopy indicated the dielectric relaxation to be of the non-Debye type. The correlated barrier hopping model was used to favourably explain the mechanism of charge transport within the material. Additionally, the prepared n-BFN exhibited a high dielectric constant (∼104) and a low tangent loss (0.35) at room temperature, making them promising candidate for microelectronic applications. Magnetic studies of the n-BFN (coercive field of 126Oe, retentivity of 0.0016 emu/g and saturation magnetization of 0.0097 emu/g) performed via vibrating sample magnetometer suggested its potential applicability in multifunctional devices.